2020
DOI: 10.1049/iet-epa.2020.0086
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of a Gramme‐ring‐winding high‐speed permanent‐magnet motor for pulsed alternator using CFD

Abstract: Due to the merit of very‐short end turns, Gramme‐ring windings are widely used in high‐speed permanent‐magnet motors (HSPMMs). This study investigated the thermal issues of a 300 kW, 12,000 rpm Gramme‐ring‐winding HPSMM with housing water jacket and forced air cooling, based on the computational fluid dynamics (CFD) and numerical heat‐transfer calculations. The reasons that cause the overheat of the prototype in the experimental test are thoroughly analysed. The high wind resistance of air gap as the ventilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It was found that as the air-cooled motor gap decreased, the flow velocity of the fluid on the stator and rotor surfaces increased for more effective heat dissipation. Wan et al [42] enlarged the internal slots of a stator core for ventilation ducts to improve stator convective heat evacuation efficiency. Husain et al [43] found that a single U-shaped arrangement of permanent magnets was more effective in cooling the rotor.…”
Section: Air Gap Convectionmentioning
confidence: 99%
“…It was found that as the air-cooled motor gap decreased, the flow velocity of the fluid on the stator and rotor surfaces increased for more effective heat dissipation. Wan et al [42] enlarged the internal slots of a stator core for ventilation ducts to improve stator convective heat evacuation efficiency. Husain et al [43] found that a single U-shaped arrangement of permanent magnets was more effective in cooling the rotor.…”
Section: Air Gap Convectionmentioning
confidence: 99%
“…where T is the servo motor torque (Nm), F is the external load force of the hydraulic cylinder (N), V is the radial piston pump displacement (m 3 /rad), and A is the effective area of the hydraulic cylinder (m 2 ). Equations (14) and (15) show that the load torque of the motor can be reduced by choosing hydraulic pump with small displacement, and the pressure of the system can be reduced by increasing the effective working area of the hydraulic cylinder or by using two cylinders in parallel connection. If the system is limited by space, forced wind cooling can be done to reduce the temperature of the PMSM.…”
Section: Thermal Balance Analysis Of the Ehspcsmentioning
confidence: 99%
“…References [13,14] presented an electromagnetic-thermal coupling analysis method of the PMSM, which was based on current harmonics and improved the (µ + 1) evolution strategy. In [15], the thermal issues of a high-speed permanent-magnet motor were studied based on CFD and numerical heat-transfer calculations, and the reasons for the overheat of the prototype in the experimental test were thoroughly analyzed. In [16], a PMSM comprehensive CFD model was presented, and the comparison between measured and simulated temperatures showed that the model sufficiently described the thermal behavior of the motor.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the power density, the generator is designed with the higher electromagnetic load and smaller size [4][5][6]. However, it leads to the increase in generator loss density and the deviations in the stiffness of the generator structure, causing the machine vibration and high temperature problems [7][8][9]. It directly affects the performance and reliability of the generator.…”
Section: Introductionmentioning
confidence: 99%